Tradisi pada rumah adat suku Ngalum Ok di era modernisasi - V. F. Agung Langgeng Prasetyo (ARTEKS : Jurnal Teknik Arsitektur, 2019)
Ngalum Ok is one among a large number of tribes in Indonesia. It is one of the major tribes in Papua and its members are those who inhabit Oksibil valley in Pegunungan Bintang Regency of Papua Province. The cultural values of this tribe are reflected in the form, function, and meaning of its traditional house architecture. In response to current developments that incline to modernization, attempts should be made to protect architecture of traditional house of Ngalum Ok Tribe, which is a cultural heritage for the present and future generations. To provide a coherent and complete macro and micro description about the traditional house of Ngalum Ok Tribe, a qualitative method with a descriptive structuralism approach is used. As the result indicates, this study has presented a clear and thorough description of form, function, and meaning of the traditional house of Ngalum Ok Tribe, which is a cultural heritage in this modern era for the present and future generations. © 2019 V. F. Agung Langgeng Prasetyo